Recording and Reporting Database Design of Patients with Multidrugs Resistance Organisms - Mualif Arsyad; Novita Arbianti (Humanistic Network for Science and Technology (HNST), 2018)
Multidrugs Resistance Organisms (MDROs) resulted by unsuitable antibiotics using and calculated 700,000 deaths per year of bacteria immune that predicted 10 million people killed in 2050. Documentation of MDROs in hospitals is a way to identify non-compliance antibiotics during treatment with periodically recording method of antibiotic. Web using become a facility to recorded antibiotik used and the method was developed in this research. Study document used that related MDROs in hospital of web model development, the study results are discussed with users of the system. Discussion results written into data needed table to identified the development web model. Normalization the databases and connecting between existing entities in the database into the Entity Relationship Diagram (ERD), it becomes a whole model database on the web model. The simulation results revealed that web models designed to identify patients with MDROs risk are effective to use especially for routine hospital data recording. Keywords: MDROs, Web design, Recording system, ER